Jockey's interest in traditional horse racing sports championships in central aceh district - Akbar, Aldiansyah; Hanafi, Hanafi (Universitas Malikussaleh, 2021)
The purpose of this study was to determine the interest of jockeys in traditional horse racing championships in Central Aceh Regency. This type of research is descriptive research with a qualitative research approach. The sample in this study amounted to 30 people. Data collection techniques by conducting observations, closed interviews and distributing questionnaires. The research instruments used were observation, interviews, and questionnaires. Data processing techniques using the percentage formula. The results showed that the jockey's interest in horse racing was in the high category with a percentage of 100%. The conclusion of the research is that the support from various parties, both from the family, the environment, and the government, makes the children develop their interest in becoming horse racing jockeys.